PENGARUH SISTEM MERIT DALAM REKRUTMEN DAN PROMOSI TERHADAP KINERJA APARATUR SIPIL NEGARA - Jeane Nikijuluw; Marthin Maspaitella (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The merit system in the recruitment and promotion of Civil Servants (ASN) serves as the foundation for building a professional and high-performing bureaucracy. This study analyzes the influence of merit system implementation on ASN performance using a systematic literature review approach. The results indicate that a consistently applied merit system is positively correlated with improvements in public organization performance. These findings are consistent with international best practices, which show that competency-based recruitment and performance-based promotion produce more competent and motivated personnel. An analysis of 45 scholarly publications from international databases identified five main dimensions of the merit system that impact performance: transparency in the selection process, objectivity in assessment, competence as the primary criterion, protection from political intervention, and a performance-based career development system.